Penerapan Kurikulum Pelatihan Berbasis Kompetensi pada Program Digital Business Management di Lembaga Pendidikan dan Pengembangan Profesi (LP3I) Banten - Darmawan, Dadan; Ganiadi, Mochamad; Mulyanto, Fiola Dwi (AJAD : Jurnal Pengabdian kepada Masyarakat, 2025)
This study aims to describe (1) the process of developing a competency-based training curriculum, (2) the implementation of the competency-based training curriculum, (3) the outcomes of the competency-based training curriculum. This research employs a descriptive method with a qualitative approach. Data collection techniques used include observation, interviews, and documentation. The research data sources consist of 9 individuals. The findings of this study indicate that the development, implementation, and outcomes of the competency-based training curriculum at LP3I Banten have been conducted quite well. However, there is a need for autonomous rights for LP3I Banten as a branch to independently design its learning plans, ensuring that they are measurable and tailored to regional needs. LP3I Banten serves as a bridge between the functions of education and training and industrial needs, ensuring that the human resources produced align with the available industry demands.